Charlotte Mary Yonge Writing the Victorian Age - Walker Gore, Clare; Schultze, Clemence; Courtney, Julia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This interdisciplinary collection of essays explores the life and work of Charlotte M. Yonge, a highly influential and popular nineteenth-century writer who is emerging from a long period of critical neglect. Its wide-ranging chapters capture the scope and quality of current work in Yonge studies, addressing the full range of her prolific literary output from her best-selling novels to her nature writing, biographies, and letters. Considering themes from gender, disability, and empire, to Tractarianism, secularism, and the idea of progress, these essays consider how Yonge reflected and shaped the tastes, ideas and anxieties of her readers and contemporaries. Exploring her key role in the Anglican revival, her importance as a test case in the development of feminist criticism, and her formal innovativeness as a novelist, this collection places Yonge centrally in the nineteenth-century literary landscape and demonstrates her ongoing relevance to scholars and students of the period. Clare Walker Gore is a lecturer in English Literature at the Open University. She held a Junior Research Fellowship at Trinity College, Cambridge, and was named a BBC/AHRC 'New Generation Thinker'. Her book, Plotting Disability in the Nineteenth-Century Novel, appeared in 2019. She is pursuing a project on Victorian women writers. Clemence Schultze is an Honorary Research Fellow in the Department of Classics at Durham University, after a career lecturing on ancient history. She has published on nineteenth-century classical reception, was for ten years Chair of the Charlotte M. Yonge Fellowship, and has co-edited an essay collection on Yonge. Julia Courtney is retired from the Open University where she was an administrator, associate lecturer and research fellow. She has published articles and book chapters on aspects of Victorian literature and culture and has co-edited two essay collections. She is co-editor, with Clemence Schultze, of the Charlotte M. Yonge Fellowship Journal.
1. Charlotte M. Yonge and the Concept of Conservative Community - Rosemary Mitchell -- 2. A Woman's Outlook: Charlotte Yonge's Sense of Place - Julia Courtney -- 3. Charlotte M. Yonge, Empire and the Wider World - Terry Barringer -- 4. Charlotte M. Yonge and the Long Victorian Family: Instructing the "Mother-Sister" - Tamara Wagner -- 5. Disability and Bioethics in Yonge's Novels - Martha Stoddard Holmes -- 6. "What I can myself remember": Charlotte M. Yonge's Life Writing - Valerie Sanders -- 7. 'Hard cash is a necessary consideration': Money and Class in Charlotte M. Yonge's Fictional Portrayals of Contemporary Family Life - Susan Walton -- 8. 'A lady with a profession': Governesses in the Novels of Charlotte M. Yonge - Clare Walker Gore -- 9. Providence and Progress: Science, Education and the Professions in Charlotte M. Yonge - Clemence Schultze -- 10. Charlotte M. Yonge and the Vocation of Childhood: Youth and Social Critique in Yonge's novels - Gavin Budge -- 11. Changing Anglican Religious Practice, the Material Culture of Church Building, and the Novels of Charlotte M. Yonge (William Whyte) -- 12. Yonge's Missions: At Home and Abroad - Barbara Dennis -- 13. "I am too high church and too narrow": Charlotte M. Yonge and Alexander Macmillan - Ellen Jordan -- 14. Charlotte Yonge and Feminist Criticism - Talia Schaffer.
Keywords: Literature, Modern-19th century; Literature; Anglican Communion; Nineteenth-Century Literature; Literature; Women's Studies; Anglicanism